Phenomenological Study of Muslim Nurses’ Experience During End-Of-Life Decision Making - Hidayat, Arif Imam; Kongsuwan, Waraporn; Nilmanat, Kittikorn; Siwi, Adiratna Sekar; Alivian, Galih Noor (Jurusan Keperawatan FIKES UNSOED, 2021)
ABSTRACTObjectives: This study examines the significance of Muslim nurses' lived experiences in the Intensive Care Unit (ICU) when it comes to End-of-Life (EOL) decisions (ICU)Methods: The research was carried out at an intensive care unit (ICU) of a government hospital in Central Java, Indonesia. Fourteen nurses were chosen as participants after meeting the inclusion criteria: Muslims with at least three years of experience in the ICU and experienced to involved in end of life decision making process in an ICU. Data were gathered using in-depth interview. The result the transcribed and analyzed by using van Manen’s hermeneutic phenomenological approach. Trustworthiness was established following Lincoln and Guba's criteria.Results: Four theme themes emerged from nurses' engagement in EOL decision-making. Feeling dilemma, being in uncertain time, receiving overwhelming role, and evading the process. Van Manen's four lived world of body, time, relation, and space are reflected in these subjects.Conclusion: The purpose of this study was to illustrate the meaning of Muslim nurses' EOL decision-making in the ICU and to affect nursing policy addressing EOL decision-making education in ICU settings.